2021
DOI: 10.1111/1750-3841.15653
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and dietary exposure assessment of pentachlorophenol in livestock, poultry, and aquatic foods marketed in Guangdong Province, China: Based on food monitoring data from 2015 to 2018

Abstract: As a persistent organic pollutant, pentachlorophenol (PCP) has serious impacts on human health. However, its presence in animal source food products sold in the Guangdong Province (GD) of China, and the resultant dietary exposure have not been elucidated. To address this gap, 3,100 samples from seven food categories, including beef, pork, mutton, offals, broilers, hen eggs, and farmed freshwater fish, marketed throughout four geographical regions of GD, were collected from 2015 to 2018. Gas chromatography coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Thus, our findings suggested that carbamate, organochlorine, organophosphate pesticides, and the fungicide OPP may primarily disturb the gut microbiome, while pyrethroid pesticides may have a greater effect on FMO (Figure ). PCP is a metabolite of organochlorine pesticides (e.g., hexachlorobenzene and lindane) and persists in various food products, especially in meat and freshwater fish, and the consequent health hazards were noteworthy as reported by the previous studies. , Additionally, experiments in goldfish showed that PCP exposure shifted the gut microbial community, which may be associated with hepatic damage …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Thus, our findings suggested that carbamate, organochlorine, organophosphate pesticides, and the fungicide OPP may primarily disturb the gut microbiome, while pyrethroid pesticides may have a greater effect on FMO (Figure ). PCP is a metabolite of organochlorine pesticides (e.g., hexachlorobenzene and lindane) and persists in various food products, especially in meat and freshwater fish, and the consequent health hazards were noteworthy as reported by the previous studies. , Additionally, experiments in goldfish showed that PCP exposure shifted the gut microbial community, which may be associated with hepatic damage …”
Section: Discussionmentioning
confidence: 74%
“…PCP is a metabolite of organochlorine pesticides (e.g., hexachlorobenzene and lindane) and persists in various food products, especially in meat and freshwater fish, and the consequent health hazards were noteworthy as reported by the previous studies. 73,74 Additionally, experiments in goldfish showed that PCP exposure shifted the gut microbial community, which may be associated with hepatic damage. 75 trans-DCCA is one of the major metabolites of pyrethroid pesticides, which are the primary constituents of indoor mosquito-repelling products.…”
Section: Discussionmentioning
confidence: 99%
“…Pentachlorophenol (PCP) and its salts are synthetic polychlorinated organic chemicals [1]. Owing to its excellent insecticidal and herbicidal properties, PCP has been widely used as an insecticide, fungicide, algaecide, herbicide, water clarifier, disinfectant, and wood preservative in agricultural and industrial fields since the 1930s [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the health risk of dietary exposure to PCP was evaluated by deterministic [1] and probabilistic assessment [13], respectively. However, the bioaccessibility and bioavailability of PCP have not been considered in these two researches, and to the best of our knowledge, no report has studied the effects of the food matrix and cooking process on the bioaccessibility and bioavailability of PCP in foods [31].…”
Section: Introductionmentioning
confidence: 99%
“…Pentachlorophenol is a serious concern regarding bioaccumulation due to its presence in meat and fish products [ 13 ]. Results obtained by Hong et al [ 14 ] from the Pearl River Delta, China, showed levels of 30 ng g −1 of pentachlorophenol in the sediment of the local drinking water source, and in human breast milk to give a daily intake of up to 10 μg infant −1 ·day −1 .…”
Section: Introductionmentioning
confidence: 99%